2019
DOI: 10.3390/jcm8070945
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Diagnosis for Internet Gaming Disorder: Comparison of DSM-5 IGD and ICD-11 GD Diagnosis

Abstract: The American Psychiatric Association (APA) included internet game disorder (IGD) in section III of the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (DSM-5) on the condition that it guaranteed more clinical research and experience. The World Health Organization (WHO) also included Game Disorder (GD) in the 11th final revision of the International Classification of Diseases (ICD-11) and recently recognized it as a diagnosis code. This study aims to compare clinical characteristics and gami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 25 publications
5
121
0
12
Order By: Relevance
“…In line with these findings, Jo et al (2019) showed that about one fifth of children and adolescents with DSM-5 IGDS met the ICD-11 GD criteria. As the ICD-11 seems to imply a higher diagnostic threshold than the DSM-5 [22,23], one could argue that incidence rates of pathological gaming might be underestimated by GD criteria. However, the IGD criteria were derived by the criteria for substance use disorders.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…In line with these findings, Jo et al (2019) showed that about one fifth of children and adolescents with DSM-5 IGDS met the ICD-11 GD criteria. As the ICD-11 seems to imply a higher diagnostic threshold than the DSM-5 [22,23], one could argue that incidence rates of pathological gaming might be underestimated by GD criteria. However, the IGD criteria were derived by the criteria for substance use disorders.…”
Section: Introductionsupporting
confidence: 70%
“…According to ICD-11 HG, they show a gaming behavior that increases the risk of substantial negative consequences [17]. In line with these findings, Jo et al (2019) showed that about one fifth of children and adolescents with DSM-5 IGDS met the ICD-11 GD criteria. As the ICD-11 seems to imply a higher diagnostic threshold than the DSM-5 [22,23], one could argue that incidence rates of pathological gaming might be underestimated by GD criteria.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, the key differentiating factor between the DSM-5 and ICD-11 framework is that significant impairment is required in the ICD-11 framework, but optional in the DSM-5 framework. There is empirical evidence to suggest that the ICD-11 framework captures a more severe population than does the DSM-5 framework (Jo et al, 2019).…”
Section: What Is Internet Gaming Disorder?mentioning
confidence: 99%
“…When the criteria determined by the DSM-V for Internet gaming disorder are applied to SMD, it could be manifested in symptoms such as excessive use, preoccupation with social media and inability to control the urge to use social media or the period of usage. In addition, the individual deceives others in order to continue usage, experiences loss of interest in other activities and employs social media to escape negative feelings 5 . Based on the criteria for Internet related addictions, SMD can be described as frequent and excessive use of social media that causes significant distress and impairment, resulting in dependence symptoms 6 .…”
Section: Billion Andmentioning
confidence: 99%